Optimality conditions for weak and firm efficiency in set-valued optimization - Durea, M. (Journal of mathematical analysis and applications, 2008)
This paper concerns the study of weak and firm local efficiency in constrained mathematical problems governed by set-valued mappings. We derive optimality conditions by means of the Bouligand derivative and by means of the Mordukhovich coderivative as well.